Essential Physical Examination of Cows: Efforts to Control Livestock Diseases in Gampong Krueng Itam, Tadu Raya District, Nagan Raya Regency - Yunus, Mukhlis (Jurnal Pengabdian Bakti Akademisi, 2024)
This service activity was conducted to provide education related to physical health checks on cows to control disease in Gampong Krueng Itam, Tadu Raya District, Nagan Raya Regency. The aim of holding this service activity is to help the community check the condition of livestock and control various types of diseases that occur. This service is carried out using counseling methods on several local community farms and conducting direct inspections of the cows on the farms. The technique used in this examination is to carry out a simple diagnosis of the cow's physical health. This activity impacts the community to determine whether domesticated cows are healthy. The recommendation regarding this activity is that there is a great need for a routine inspection agenda for cattle and other educational activities to increase public knowledge regarding livestock health.